Mojo journalism: emerging opportunities - Beldibekova Әлия (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
What is mobile journalism? Combining digital storytelling tools and techniques to transform raw user-generated content into rich reporting. Simply put, mobile journalism is your phone and microphone. The development of iOS and Android opens up new opportunities in the information society. Today, modern technologies such as smartphones and the Internet are changing the nature of media and even journalism. Mojo is mobile journalism. Offers the ability to create high-quality reports using mobile devices. Mobile journalism is swift and interactive. So versatile. This is the result of true convergent journalism. The product, created using smartphones and tablets, is not inferior to videos and photographs shot on professional equipment and also allows you to effectively meet the growing needs of the audience for mobile content. With the help of the high-quality Internet, you can make quick edits and write quality information through social networks. The main advantages are accessibility, privacy, and speed. However, there may be some shortcomings in terms of quality. The quality of the video, however, depends on the journalist’s smartphone. The better the device, the better the product. Stephen Mann, a journalist, was the first to use mobile journalism. In his first report, he published confidential information that other journalists were unable to obtain through mobile journalism. The article examines mobile journalism’s place in the media system and its modern demand. The article takes into account the evolution of this field and the characteristics of using mobile devices in journalism. The advantages, disadvantages, and opportunities for the development of mobile journalism were noted. Its place in relation to traditional journalism is determined.